Quantitative Analysis of Heavy Metals in Water Based on LIBS with an Automatic Device for Sample Preparation *supported by National Natural Science Foundation of China (No. 60908018), National High Technology Research and Development Program of China (No. 2013AA065502) and Anhui Province Outstanding Youth Science Fund of China (No. 1108085J19). (August 2015) - Hu, Li; Zhao, Nanjing; Liu, Wenqing; Meng, Deshuo; Fang, Li; Wang, Yin; Yu, Yang; Ma, Mingjun
Abstract Heavy metals in water can be deposited on graphite flakes, which can be used as an enrichment method for laser-induced breakdown spectroscopy (LIBS) and is studied in this paper. The graphite samples were prepared with an automatic device, which was composed of a loading and unloading module, a quantitatively adding solution module, a rapid heating and drying module and a precise rotating module. The experimental results showed that the sample preparation methods had no significant effect on sample distribution and the LIBS signal accumulated in 20 pulses was stable and repeatable. With an increasing amount of the sample solution on the graphite flake, the peak intensity at Cu I 324.75 nm accorded with the exponential function with a correlation coefficient of 0.9963 and the background intensity remained unchanged. The limit of detection (LOD) was calculated through linear fitting of the peak intensity versus the concentration. The LOD decreased rapidly with an increasing amount of sample solution until the amount exceeded 20 mL and the correlation coefficient of exponential function fitting was 0.991. The LOD of Pb, Ni, Cd, Cr and Zn after evaporating different amounts of sample solution on the graphite flakes was measured and the variation tendency of their LOD with sample solution amounts was similar to the tendency for Cu. The experimental data and conclusions could provide a reference for automatic sample preparation and heavy metal in situ detection.